Quality of Tests on Mathematics Questions for Year-End Assessment (PAT) Class VIII at SMPN 2 Bangkinang Kota - Anggraini, Yola Putri; Roza, Yenita; Maimunah, Maimunah (Universitas Negeri Makassar, 2020)
This study aims to determine the quality of the test on multiple choice questions in mathematics for Year End Assessment (PAT) class VIII SMPN 2 Bangkinang Kota for the 2019/2020 academic year based on the level of question validity, reliability level, difficulty level, distinguishing power, and option effectiveness cheater). This research is an evaluation with a quantitative descriptive approach. The research was conducted with a sample of 30 student answer sheets. Techniques for collecting data are documentation techniques. After the data is collected, the data will be analyzed with the help of Excel. Judging from the results of this analysis, it can be seen that the End of Year Assessment (PAT) questions for class VIII SMPN 2 Bangkinang Kota for the 2019/2020 academic year were not carried out by quantitative reviewers. Judging from the level of validity, it consists of 14 valid questions, while the other 16 questions are said to be invalid. The PAT questions have a high level of reliability. As for the difficulty level of the questions, there are 7 items (23.33%) difficult, 18 items (60%) moderate, and 5 items (16.66%) easy. The distinguishing power is 8 questions that are bad (26.66%), 7 questions with sufficient criteria (23.33%), 7 questions with good criteria (23.33%), and 8 questions with very good criteria (26.66%) ). For the effectiveness of the option, 4 items (13.33%) were very good, 15 items (50%) were good, 9 items (30%) were bad, and 2 items (6.33%) were very bad. So that based on the results of the quantitative test, it turns out that most of the items were not of good quality for Class VIII Year End Assessment (PAT) for the 2019/2020 school year.